Engineering students’ readiness and preparedness on teaching materials with Microsoft Teams and Microsoft Sway / Amizon Azizan - Azizan, Amizon (2021)
Microsoft Teams (MT) and Microsoft Sway (MS) are parts of Microsoft 365. The online distance learning (ODL) has opened for wide opportunities for educators to venture into these attractive platforms in teaching and learning (T&L). The students’ preparedness can be indirectly measured via Microsoft Forms as alternative method besides recording students’ attendance but also at the same time, viewing their opinions and status about T&L. It was found that most students are fully prepared with all the information supplied via MT announcements about T&L materials via MT and MS